STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR AKIDAH AKHLAK KELAS XI DI MAN 3 ACEH BESAR - Rahma Wanda Noviani; Fadhilah; Syafruddin; Zulkarnaini (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2025)
Learning strategies are plans that encompass a series of activities, methods, and the utilization of resources to achieve educational objectives. In formal education, teachers act as administrators who must be capable of organizing educational programs optimally. Therefore, teachers need to possess engaging and enjoyable learning strategies to enhance students’ learning motivation. In the subject of Aqidah Akhlak, learning does not only focus on cognitive aspects but also emphasizes the practice of moral values in daily life. Consequently, teachers must serve as good role models both inside and outside the school environment. This study aims to identify the learning motivation of ninth-grade students in the Aqidah Akhlak subject, examine the planning and implementation of teachers’ strategies in enhancing such motivation, and analyze the obstacles faced by teachers at MAN 3 Aceh Besar. Data were collected through observation, interviews, and documentation. The results indicate that teachers’ efforts to improve students’ learning motivation have been fairly successful. Students show increased interest in learning, and teachers believe that positive changes will continue as students become more aware that this learning is beneficial for their personal development.